Fatu-Hiva back to nature - Heyerdahl, Thor (Doubleday Company, Inc., 1975)
The story of Heyerdahl and his wife's first Pacific adventure in 1936. Fatu-Hiva lay outside the shipping lanes; there were no white inhabitants and no contact with the outside world.